Characteristics of anal canal cancer in Japan. (10th March 2022) - Yamada, Kazutaka; Saiki, Yasumitsu; Komori, Koji; Shiomi, Akio; Ueno, Masashi; Ito, Masaaki; Hida, Koya; Yamamoto, Seiichiro; Shiozawa, Manabu; Ishihara, Soichiro; Kanemitsu, Yukihide; Ueno, Hideki; et al.
Abstract: Anal canal cancer (ACC) has been reported to be an uncommon cancer in Japan, as in the USA, Europe, and Australia. This retrospective multi‐institutional study was conducted to clarify the characteristics of ACC in Japan. First, the histological ACC type cases treated between 1991 and 2015 were collected. A detailed analysis of the characteristics of anal canal squamous cell carcinoma (SCC) cases was then conducted. The results of the histological types revealed that of the 1781 ACC cases, 435 cases (24.4%) including seven cases of adenosquamous cell carcinomas were SCC and 1260 cases (70.7%) were adenocarcinoma. However, the most common histological type reported in the USA, Europe, and Australia is SCC. Most ACC cases are adenocarcinomas and there is a low incidence of SCC in Japan which is different from the above‐mentioned countries. Moreover, we reclassified T4 into the following two groups based on tumor size: T4a (tumor diameter of 5 cm or less) and T4b (tumor diameter of more than 5 cm). The results of the TNM classification of SCC revealed that the hazard ratio (HR) to T1 of T2, T3, T4a, and T4b was 2.45, 2.28, 2.89, and 4.97, respectively. As T4b cases had a worse prognosis than T4a cases, we propose that T4 for anal canal SCC in Japan be subclassified into T4a and T4b. Abstract : Most anal canal cancers in Japan are adenocarcinomas, the squamous cell carcinomas rate is low. In the T4 factor based on the depth of tumor invasion, there was a difference in prognosis depending on the tumor diameter and therefore we propose creating the subclassifications T4a and T4b for anal canal SCC in Japan.